Sustainability consciousness among pre-service teachers at the Institute of Teacher Education Malaysia: expert review and exploratory factor analysis - Farah Izyan Raman; Fonny Dameaty Hutagalung; Mohd Nazri Abdul Rahman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Sustainability consciousness (SC) is an approach to assessing all elements of sustainable development from a holistic perspective. Global studies within teacher education settings began to pay attention to research on SC. The aim of this study was to adapt and examine an instrument for measuring SC among pre-service teachers at the Institute of Teacher Education Malaysia. The researchers adapted 27 items from the previous study for the SC construct. Expert panels verified the instrument's content, face, and criterion validity. Accordingly, the item statements were modified based on the feedback of experts. 111 pre-service teachers from six Institutes of Teacher Education in the Central Zone, South Zone, Sarawak Zone, and Sabah Zone were selected at random for the pilot test. The data were analyzed and verified using exploratory factor analysis (EFA). The outcome of the EFA procedure indicated that the 27 items may be categorized into three components. The items under these three components explained 65.1% of the total variance. The SC scale has an internal reliability of 0.96. In regard to contributing to the existing body of knowledge, the results provide a credible source of information for future studies on the SC of pre-service teachers to researchers and professionals.